2015
DOI: 10.1111/isj.12068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of technostress and switching stress on discontinued use of social networking services: a study of Facebook use

Abstract: Although much research has been performed on the adoption and usage phases of the information systems life cycle, the final phase, termination, has received little attention. This paper focuses on the development of discontinuous usage intentions, i.e. the behavioural intention in the termination phase, in the context of social networking services (SNSs), where it plays an especially crucial role. We argue that users stressed by using SNSs try to avoid the stress and develop discontinuous usage intentions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
471
8
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(505 citation statements)
references
References 80 publications
(265 reference statements)
23
471
8
3
Order By: Relevance
“…Hence, in the "person" component, we include all the constructs that can influence the perception and appraisal processes. Exemplary constructs include individual characteristics, such as personality variables (e.g., D'Arcy et al, 2014;Emurian, 1993;Maier et al, 2015b; or attitudes toward technology or one's own ability to handle technology (e.g., Tarafdar, Pullins, & RaguNathan, 2014.…”
Section: Components Of Technostressmentioning
confidence: 99%
“…Hence, in the "person" component, we include all the constructs that can influence the perception and appraisal processes. Exemplary constructs include individual characteristics, such as personality variables (e.g., D'Arcy et al, 2014;Emurian, 1993;Maier et al, 2015b; or attitudes toward technology or one's own ability to handle technology (e.g., Tarafdar, Pullins, & RaguNathan, 2014.…”
Section: Components Of Technostressmentioning
confidence: 99%
“…First, Harman's single factor test indicated that only 43% of the variance accounted to one factor, which is below the threshold of 50% and, thus, gives initial support for the absence of high CMB [60]. Second, we performed a latent common method factor analysis [60,61,62], a frequently employed test in IS research [e.g., 26,63]. Hereto, an additional CMB factor containing all indicators is added to the model and all indicators of the theoretical constructs are transformed into singleitem factors [62].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Results by Maier et al (2015) show that SNS (Social Network Services) -stress creators and SNS-exhaustion cause discontinuous usage intentions, and switching-stress creators and switching-exhaustion reduce these intentions.…”
Section: Discussionmentioning
confidence: 99%